Pengaruh Senam Lansia Aerobic Low Impact Training Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi - Widjayanti, Yhenti; Silalahi, Veronika; Merrianda, Priska (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Hypertension is a disease with a systolic > 140 mmHg and a diastolic > 90 mmHg. This disease often occurs in the elderly due to aging as cell, physiological, and psychological changes occur. Phenomenon found in Griya Usila Santo Yosef many elderly were hypertensive suferer. One non-pharmacological management for hypertension is low impact training aerobic exercise. This study aims to analyse effect of low impact training aerobic exercise on decreasing blood pressure in elderly with hypertension. Desiign of this study was a pre-experimental design with a one group pre-post test design. The independent variable in this study was low impact aerobic exercise, and the dependent variable was blood pressure. Respondents of this study were 32 elderly people with hypertension who fulfilled the inclusion criteria whom were collected by simple random sampling. Results of this study showed that mean of systolic and diastolic blood pressure before intervention was 149.84 ± 6.66 and 83.25 ± 11.41, mean systolic and diastolic blood pressure after intervention was 145.09 ± 5.71 and 79.44 ± 11, 55, and the results of paired T-Test statistical tests with SPSS 20 software were obtained p (0,000) <α (α = 0.05) for the systolic and diastolic pressure. It meant that there was an influence of low impact aerobic exercise on blood pressure reduction. Based on the results of the research, elderly gymnastics aerobic low impact is important in which the training given to elderly patients hypertension to help in controling blood pressure. Keywords: Hypertension, Elderly, Aerobic Low Impact Exercise